PERHITUNGAN PREMI ASURANSI JIWA DWIGUNA DIBAYARKAN PADAAKHIR TAHUN KEMATIAN DENGAN MENGGUNAKAN PACKAGE PERANGKAT LUNAK R - Hikmah, Yulial; Hikmah, Ira Rosianal (Jurnal Vokasi Indonesia, 2020)
In calculating premiums, many insurance companies use commutation tables. Premium calculation can also be done with R software by making the function. Besides that, there is a set of packages available to make it efficient in solving various problems. One of the R packages in the field of insurance and actuarial is lifecontingencies, which can be used to manage life tables, actuarial tables, and perform calculations in actuarial mathematics. To calculate premiums for some customers, the use of lifecontingencies package is more efficient in terms of time because the calculations are carried out simultaneously for all customers compared to calculations using commutation tables manually. Therefore, this research discusses how to calculate the annual premium on an n-year end-to-end life insurance product by using a commutation table manually and by using the lifecontingencies package in Software R based on the illustration given. The results show that by using the commutation table manually and by using lifecontingencies package, the premium calculation results are the same. So, it can be concluded that the calculation of the premium with lifecontingencies package on R is better than the manual calculation because the premium results are the same but with a shorter time.